2014
DOI: 10.1155/2014/893158
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni Doped ZnO-TiO2Composites and Their Enhanced Photocatalytic Activity

Abstract: Herein, Ni doped ZnO-TiO2composites were prepared by facile sol-gel approach and were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), UV-visible diffuse reflectance spectroscopy (UV-Vis DRS), X-ray photoelectron spectroscopy (XPS), and photoluminescence spectroscopy (PL). The results indicated that the Ni ions can be incorporated into the lattice of TiO2structure and replace Ti. The introduction of Ni expanded light absorption of TiO2to visible region, increased amount of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…This probably due to small dopant concentration of ZnO used in this study which is only 0.75%. This finding is in agreement with the reported studies where disappearances of ZnO peaks is attributed to the very small of crystallite size [3]. Figure 3(a) illustrates the highest intensity at 600 o C and sharpen peaks indicate at higher calcination temperature up to 600 o C promotes higher crystallinity of catalyst forming.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This probably due to small dopant concentration of ZnO used in this study which is only 0.75%. This finding is in agreement with the reported studies where disappearances of ZnO peaks is attributed to the very small of crystallite size [3]. Figure 3(a) illustrates the highest intensity at 600 o C and sharpen peaks indicate at higher calcination temperature up to 600 o C promotes higher crystallinity of catalyst forming.…”
Section: Resultssupporting
confidence: 92%
“…Specifically, absorption of TiO 2 can be extended to visible range [3] when coupling with other semiconductor or doping with non-metal or metal ion such as B, C, N, Fe 3+ and Zn 2+ [4] or metal oxides such as ZnO and MgO. Previous works reported that ZnO appeared as promising photocatalyst and alternative to TiO 2 since its photo degradation mechanism was identical to TiO 2 .…”
Section: -2506mentioning
confidence: 99%
“…Thus, B, ZnO, and TiO 2 altogether resulted in a synergistic effect to obtain enhanced photocatalytic performance of B-ZnO/TiO 2 [17,26]. Furthermore, B-ZnO/TiO 2 nanocomposites exhibit superior photocatalytic performance compared to other nanocomposites presented in the literature [17,18,20,[40][41][42][43][44][45], as summarized in Table 2, indicating that B-ZnO/TiO 2 can be a promising photocatalyst for the removal of organic dyes.…”
Section: Photocatalytic Removal Of Mb Dyementioning
confidence: 89%
“…e absence of other Zn 2p peaks indicates that zinc ions form ZnO and that they are not part of the TiO 2 lattice. e XPS O 1s spectra (Figure 2(d)) for all nanocomposites are also identical and are characterized by peaks at 529.2 eV and 531.7 eV, which correspond to oxygen bound in the crystal lattice of metal oxides and hydroxyl oxygen (OH) on the sample surface, respectively [53].…”
Section: Xps Surface States Ofmentioning
confidence: 93%